Osteoarthritis and age. Role of aging in the etiology and pathogenesis of the disease - L. V. Luchikhina; O. I. Mendel; V. Mendel; G. N. Golukhov (Современная ревматология)
The paper considers current views on the mechanisms for the development and progression of osteoarthritis (OA) and gives the definition of the disease. It describes the processes underlying aging and OA at the molecular and cellular level, with emphasis on the role of chronic nonspecific inflammation. The possible mechanisms of chronic age-related inflammation (inflammaging), the mainstay of which is systemic aging of the immune system, are characterized. On the basis of the data available in the literature, it is concluded that aging and OA have common intracellular transcription cascades and pathophysiological mechanisms: chronic nonspecific inflammation and metabolic disorders are substantially implicated in the pathogenesis of these conditions. Metabolic and structural changes occurring in the cartilage and other tissues of the locomotor apparatus with aging are noted to serve as a favorable platform for the further development and progression of OA.